PENGEMBANGAN E-MODUL BERBANTUAN GEOGEBRA PADA MATAKULIAH KALKULUS INTEGRAL LIPAT - Venty Meilasari; Khusnul Khotimah (SIGMA, 2022)
The lack of interaction between students and lecturers in learning causes information not to be conveyed optimally. Moreover, fold integral calculus is an abstract material. Therefore, learning innovations are applied that can support more independent learning and are able to visualize abstract material. This study aims to determine the feasibility of the geogebra-assisted electronic module in the fold integral calculus course. This research is classified as development research which refers to Sugiyono development model but is only limited to 7 stages. The stages carried out in the research, namely potential and problems, data collection, product design, design validation, design revision, product testing and product revision. The instruments used in this study were validation sheets, user response questionnaires, and learning outcomes tests. Indicators of achievement of the results of this study are e-modules are declared suitable for use and students who get optimal learning outcomes are more than 70%. The results showed that the folding integral calculus e-module that was made was feasible to use. This is shown as much as 74% of students achieve optimal learning outcomes.